SsDiHal: discovery and engineering of a novel tryptophan dihalogenase - Hassan Sher; Haley Hardtke; Wenzhu Tang; Jie Ren; Hayat Ullah; Xudong Zhou; Y. Jessie Zhang; Jixun Zhan (Journal of Biological Engineering)
Abstract Background Halogenation plays a crucial role in enhancing the properties of small molecules, particularly by making them more effective for applications in agrochemicals and pharmaceuticals. Notably, approximately a quarter of current pharmaceuticals are halogenated. While chemical halogenation remains the most widely employed method for producing halogenated molecules, it has significant drawbacks, including extreme reaction conditions, heavy pollution, and the use of toxic reagents. In contrast, bio-halogenation offers a “greener” approach to generating halogenated compounds. However, its industrial application is limited due to the low activity and stability of naturally occurring halogenase enzymes. Results In this study, we identified a novel tryptophan halogenase, SsDiHal, from Saccharothrix sp. NRRL B-16348 through genome mining. We found that SsDiHal catalyzes a two-step chlorination of tryptophan to sequentially yield 7-chlorotryptophan and 6,7-dichlorotryptophan, making SsDiHal the first naturally occurring tryptophan dihalogenase to be identified. Using a strcutral model of SsDiHal to guide mutagensis, several SsDiHal mutants were generated and tested for improved catalytic efficiency and altered regioselectivity. Compared to the halogenation activity of the wild type SsDiHal, the V53I, V53I/I83V and N470S mutants demonstrated significantly enhanced catalytic efficiency, with 7.7-, 4.16-, and 7.4-fold increases respectively, for the L-tryptophan substrate. While no change in regioselectivity was observed for the V53I, I83V, F112Y, and V53I/I83V mutants, a notable regioselectivity shift was found in the N470S mutant. Specifically, this mutant synthesized 6-chlorotryptophan as the first product, rather than the canonical 7-chlorotryptophan that is synthesized by wild type SsDiHal with no effect in its dihlogenation function. Conclusion Overall, this work not only adds a novel dihalogenase to the growing field of halogenating enzymes but also demonstrates that leveraging a structrual model to guide engineering of halogenases can both enhance the catalytic efficiency and modify regioselectivity of the wild type enzyme. This work holds significant potential for green applications in the agrochemical and pharmaceutical industries.